Rancang Bangun Aplikasi E-Commerce Pemesanan Jasa Fotografi Soulpict.u Berbasis Web - Fuadah, Hana Samrotul; Fitri, Sulidar; Sarmidi, Sarmidi (Computer Journal, 2025)
Soulpict.u operates a photography service business where bookings are managed through WhatsApp messages and order records are kept in handwritten notebooks. The manual documentation method has created concerns about data security and its impact on customer service quality. This research focuses on creating a web-based e-commerce platform as a digital solution for Soulpict.u, enabling structured and integrated order management. Built with PHP programming language and MySQL database system, the platform streamlines the entire booking workflow. The developed application serves multiple purposes: it simplifies the reservation process for customers, provides administrators with efficient order management tools, and enhances the overall business operations. Through systematic testing and implementation, the platform has shown marked improvements in data organization, customer communication, and service delivery. The results demonstrate the application's effectiveness in transforming Soulpict.u's manual processes into a professional digital system.